Answer:
y = -x - 2
Step-by-step explanation:
Find two points on the line
(0, -2)
(4, -6)
(Y2-Y1)/(X2-X1) = gradient of the line
Where (X1,Y1) = (0, -2) and (X2,Y2) = (4, -6)
(-6--2)/(4-0)
(-6+2)/4
(-4)/(4)
-1
Y = (-1)X + c
Substitute either set of coordinates in to find c.
(0, -2)
Y = (-1)X + c
-2 = (-1)0 + c
-2 = 0 + c
-2 = c
(4,-6)
Y = (-1)X + c
-6 = (-1)4 + c
-6 = -4 +c
-6 + 4 = c
-2 = c
Y = -X -2
As I can tell the tables are right but it would be a function since none of the x's repeat
It’s just 9 LOL yeahhhhhhhhhhhhhggg hope it goes well lollll
0, 12, 36, 108
just plug n (1,2,3,4) into the equation and that’s your answer.